Simultaneous monitoring of mouse respiratory and cardiac rates through a single precordial electrode - Motoshige Sato; Nobuyoshi Matsumoto; Asako Noguchi; Toya Okonogi; Takuya Sasaki; Yuji Ikegaya (Elsevier, 2018)
Normal respiratory and circulatory functions are crucial for survival. However, conventional methods of monitoring respiration, some of which use sensors inserted into the nasal cavity, may interfere with naïve respiratory rates. In this study, we conducted a single-point measurement of electrocardiograms (ECGs) from the pectoral muscles of anesthetized and waking mice and found low-frequency oscillations in the ECG baseline. Using the fast Fourier transform of simultaneously recorded respiratory signals, we demonstrated that the low-frequency oscillations corresponded to respiratory rhythms. Moreover, the baseline oscillations changed in parallel with the respiratory rhythm when the latter was altered by pharmacological manipulation. We also demonstrated that this method could be combined with in vivo whole-cell patch-clamp recordings from the hippocampus. Thus, we developed a non-invasive form of respirometry in mice. Our recording method using a simple derivation algorithm is applicable to a variety of physiological and pharmacological experiments, providing an experimental platform in studying the mechanisms underlying the interaction of the central nervous system and the peripheral functions. Keywords: Electrocardiograms, Respiration, Olfactory bulb, Membrane potentials, Local field potentials